Aminoquinazolin-4(3H)-one derivatives as multitargeting therapeutics in Alzheimer's disease - Tajamul Hussain; Salman Alrokayan; Dilawar Hussain; Khurram Shoaib; Syeda Abida Ejaz; Steven Ford; Jamshed Iqbal (Results in Chemistry)
Alzheimer's disease (AD) is one of the most debilitating forms of amyloidogenesis-induced dementia, and innovative, effective scaffolds are required for its treatment. Monoamine oxidase B (MAO-B) contributes to Alzheimer's by oxidizing monoamines and generating reactive oxygen species, thereby increasing oxidative stress and neuroinflammation. This makes MAO-B a promising therapeutic target to mitigate neuronal damage and slow disease progression. Beta-site APP cleaving enzyme1 (BACE1) catalyzes the rate-determining step in the production of a peptide, hence its inhibitors may play a crucial role in the treatment of Alzheimer's disease. Therefore, the successful inhibition of BACE1 by small compounds may be a viable strategy for the development of anti-AD drugs. In the current investigation, a small library of aminoquinazolinone-hydrazone derivatives underwent in-vitro and in-silico investigations. The anti-proliferative and antioxidant activities of aminoquinazolin-4(3H)-one derivatives (DH1-DH8) were evaluated, along with their cytotoxicity toward non-cancerous BHK-21 cells. Among the tested compounds, DH5 and DH7 exhibited the highest potency against cancer cells. Secondly, the study investigated their antioxidant potential using DPPH and ABTS assays. Notably, DH3, DH5, and DH8 demonstrated strong radical scavenging activity, with DH8 showing the highest ABTS scavenging potential. Structure-activity relationship (SAR) analysis revealed that electron-donating groups (-OH, -OMe) enhanced antioxidant and anti-proliferative activity, while hydrophobic (Cl) groups contributed to increased cytotoxicity against cancer cells. The newly synthesized compounds were also tested for BACE1 inhibition in-vitro using fluorescence resonance energy transfer (FRET) test methods. Among these compounds, the 2-nitrobenzylidene-containing compound (DH8) exhibited the strongest inhibitory action against BACE1, with an IC50 of 5.75 μM. Furthermore, during molecular docking studies, DH8 also demonstrated the maximum binding energy of −8.3 kcal/mol. These findings were further supported by molecular dynamics (MD) simulations, indicating the substantial stability of the protein-ligand complex. Additionally, in-silico ADME modeling was utilized to analyze the pharmacokinetic profile. Conclusively, the findings of the current study suggest hydrazineylquinazolinones as valuable scaffolds for the treatment of Alzheimer's disease by targeting BACE1.